Suffering and Tears: Authenticity and Student Volunteerism in Postreform China. (September 2017) - Sum, Chun‐Yi
Abstract: This article examines a conundrum in my ethnographic fieldwork with Chinese university students who volunteered in service trips to rural communities: why did participants volunteer to suffer and to cry? This article explains students' quest for hardship and tears in relation to emerging desires for authenticity in China. It discusses how the political state and student volunteers co‐constructed the peculiar expressions of these desires. As authentic emotions came to the forefront in students' understanding of meaningful engagement, they diluted the political connotation of volunteerism and consequently undermined the state's moral authority as the "lead volunteer." This created the room for students to align the definition of responsible citizenship with authentic commitment and youthful innocence. Delineating the paradoxes and obstacles that volunteers encountered in their quests, this article problematizes the potential and limits of authenticity in transforming the foundations of sociability and moral leadership in postreform China. 本文通过大学生对情绪表达的追求分析志愿活动在中国的冒起。作者跟随大学生往赴农村「支教」, 发现志愿者都渴慕最苦最累的体验, 以及由心而发的泪水。这些追求反映了年轻人对社会上种种造假和功利主义的不满。志愿者以汗水和泪水明志, 宣告自己参与志愿工作不为名利报酬, 只为满腔热诚所使。这种热血主导的志愿精神对参与者的道德观带来什么冲击, 如何造就年轻人对社会状况的反思? [Authenticity, Emotion, Youth, Volunteerism, China]